Relationship between physical, mechanical and thermal properties of flexible chain polymers - Kolupaev, B.B.; Kolupaev, B.S.; Levchuk, V.V. (Physics and Chemistry of Solid State, 2023)
The results of the study on the relationship between the physical, mechanical and thermal properties of linear flexible polymers due to the harmonic and anharmonic components of the interatomic and intermolecular interaction force are presented. Using the example of polyvinyl chloride (PVC), polyvinyl butyral (PVB), polystyrene (PS), it is shown that in the region of 300 K < = T < = 400 K, the relaxation state of the system is realized due to the mobility of the structural elements, which makes it possible to apply the terms of thermodynamics and statistics of small systems to the properties of the material, and to treat the polymeric state as a special form of condensation of matter. The quantitative relationship between the properties of systems has been established, which is of interest for creating scientific foundations for predicting, obtaining and operating materials under the action of external fields of various nature.